Pengelolaan Zakat Uni Emirat Arab - Bunga Anggita Batubara; Marlinda Mustika; Maryam Batubara (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Zakat in Islamic economics is able to encourage equal distribution of income and wealth by eliminating the accumulation of assets among some people. Zakat can build economic growth and equal income distribution. Each Islamic country has a different approach to managing zakat. To maximize the collection of ZIS funds, Indonesia can compare zakat collection models with Islamic countries. There are many Islamic countries that are successful in managing zakat, one of which is the United Arab Emirates. This research aims to find out how zakat is managed in the United Arab Emirates and how it differs from zakat management in Indonesia. This research uses a qualitative approach with library research methods. The results of the research are that zakat funds in the UAE are managed by the Zakat Fund under the auspices of the Minister of Islamic Affairs and Endowments. The differences lie in the structure of zakat fund collection, location of asnaf distribution, and online zakat request services.